Preparation and properties of thermoplastic starch-Ti0₂-Al₂O₃ nanocomposite - Kang, Ai Ting (2015)
In this study, preparation and properties of thermoplastic starch-Ti0₂-Al₂0₃ nanocomposite was conducted. Cassava was used as thermoplastic starch (TPS) and was plasticized with glycerol with ratio of 70/30. Then, TPS was internal mixed with Ti0₂ and Al₂0₃ by compositions of TPS-3 wt.% Ti0₂- 2 wt.% Al₂0₃, TPS-2 wt.% Ti0₂-1 wt.% Al₂0₃ and TPS-0.75 wt.% Ti02-0.25 wt.%Al₂0₃. Three different sizes of Al₂0₃ fillers were also used (0.05 vm, 1 (μm and 5 μm). TPS nanocomposite were prepared by compression molding to obtain sheet. Characterization of TPS nanocomposites were morphology, tensile properties, water absorption and density. The morphology of the nanocomposite showed that TPS-2 wt.% Ti0₂-1 wt.% Al₂0₃ have good dispersion of fillers in the matrix and exhibit the highest tensile strength. The sizes of Al₂0₃ do not affect much on the morphology of the TPS-Ti0₂-Al₂0₃ nanocomposite. Tensile strength was increased with the decreased of Al₂0₃ particle size due to the enhancement of fillers-to-polymer interaction. Morphology study also shows that Al₂0₃fillers were not completely embedded in TPS. Both Ti0₂ and Al₂0₃ fillers seem did not give significant effect on the properties of TPS-Ti0₂-Al₂0₃ nanocomposite due to too little composition in the nanocomposite.